Characterization of C2C12 cells in simulated microgravity: Possible use for myoblast regeneration. Issue 4 (24th September 2019) - Calzia, Daniela; Ottaggio, Laura; Cora, Alessandro; Chiappori, Giorgia; Cuccarolo, Paola; Cappelli, Enrico; Izzotti, Alberto; Tavella, Sara; Degan, Paolo
Abstract: Muscle loss is a major problem for many in lifetime. Muscle and bone degeneration has also been observed in individuals exposed to microgravity and in unloading conditions. C2C12 myoblst cells are able to form myotubes, and myofibers and these cells have been employed for muscle regeneration purposes and in myogenic regeneration and transplantation studies. We exposed C2C12 cells in an random position machine to simulate microgravity and study the energy and the biochemical challenges associated with this treatment. Simulated microgravity exposed C2C12 cells maintain positive proliferation indices and delay the differentiation process for several days. On the other hand this treatment significantly alters many of the biochemical and the metabolic characteristics of the cell cultures including calcium homeostasis. Recent data have shown that these perturbations are due to the inhibition of the ryanodine receptors on the membranes of intracellular calcium stores. We were able to reverse this perturbations treating cells with thapsigargin which prevents the segregation of intracellular calcium ions in the mitochondria and in the sarco/endoplasmic reticula. Calcium homeostasis appear a key target of microgravity exposure. In conclusion, in this study we reported some of the effects induced by the exposure of C2C12 cell cultures to simulated microgravity. The promising information obtained is of fundamental importance in the hope to employ this protocol in the field of regenerative medicine Abstract : Simulated microgravity effects on myogenesis; biochemical and molecular outcomes of simulated microgravity exposure; potential of simulated microgravity in regenerative medicine.